AdeB efflux pump gene knockdown by mRNA mediated peptide nucleic acid in multidrug resistance Acinetobacter baumannii. (February 2020) - Abdi, Seyed Naser; Ghotaslou, Reza; Asgharzadeh, Mohammad; Mehramouz, Bahareh; Hasani, Alka; Baghi, Hossein Bannazadeh; Tanomand, Asghar; Narenji, Hanar; Yousefi, Bahman; Gholizadeh, Pourya; Yousefi, Mehdi; Bastami, Milad; et al.
Abstract: Multidrug-resistant Acinetobacter baumannii isolates cause critical problems in health-care environments. AdeABC is a resistance-nodulation-cell division (RND)-type multidrug efflux pump conferring resistance to clinically essential antibiotics in A. baumannii, such as ciprofloxacin. This study aimed to target adeB gene with antisense peptide nucleic acid (PNA) and investigate its effect on resistance to antibiotics. NCBI database was used to design appropriate PNA to target adeB gene, by connecting PNA to mRNA, the translation of mRNA can be prevented. Three clinical isolates and A. baumannii ATCC 17978 were treated with the designed PNA by electroporation and competence procedure. Minimum Inhibitory concentration (MIC) of ciprofloxacin, colistin, and tetracycline were determined by microbroth dilution method. In addition, the expression level of adeB gene was measured by quantitative real-time PCR (qRT-PCR). Isolates used in this study had mutations in gyrA and parC genes corresponding to resistance to ciprofloxacin. MIC of resistance to ciprofloxacin after treatment with PNA was reduced from 32 μg/ml to16 μg/ml in A. baumannii ATCC 17978 isolate. Susceptibility level of tetracycline, in the 2 clinical isolates was decreased from 64 μg/ml to 32 μg/ml and in the other isolate was reduced from 128 μg/ml to 64 μg/ml. The expression level of adeB gene was decreased in A. baumannii ATCC 17978 (P > 0.01) but not in clinical isolate (P = 0.107). Findings of the present study indicate overexpression of adeB efflux pump has extra effect on resistance to antibiotics in isolates with a defined mechanism of resistance. Antisense technology is a feasible technique to suppress the function of these genes, which may be further exploited to control multidrug-resistant isolates. Highlights: Overexpression of adeB efflux pump has extra effect on resistance to antibiotics. PNA against adeB reduced resistance to Ciprofloxacin in A. baumannii ATCC 17978. PNA against adeB had less effect on clinical isolates of A. Baumannii. Antisense technology is a feasible technique to suppress the function of resistance genes.